دور أدوات السيـاسة النقديـة في تحقيق أهدافها في الاقتصاد الإسـلامي - مسعودة, نصبه (Sciences humaines, 2014)
نظرا لانفراد الاقتصاد الإسلامي عن غيره من الأنظمة الاقتصادية التقليدية من حيث طبيعته ومبادئه وكذا الأهداف التي يسعى إلى تحقيقها، فمن الطبيعي أن تختلف جوانب السياسة النقدية في الاقتصاد الإسلامي عنها في الاقتصاد التقليدي من حيث المفهوم، الأهداف والأدوات رغم وجود بعض النقاط التي يمكن أن تتفق فيها معها، ففي إطار اقتصاد إسلامي يحرم التعامل بالربا ويحل قاعدته على المشاركة كبديل  لسعر الفائدة، تتنوع أدوات السياسة النقدية بين مجموعتين: المجموعة الأولى: عبارة عن أدوات محايدة بمعنى أنها لا تتعارض مع قاعدة المشاركة وتضم: أدوات كمية، أدوات كيفية، وأدوات وأساليب التدخل المباشر.المجموعة الثانية: عبارة عن أدوات قائمة على أساس الربا وبحاجة إلى تطوير أو إصلاح حتى يمكن استخدامها في اطار اقتصاد إسلامي وذلك بتطوير الأدوات الكمية القائمة على أساس سعر    Abstract :   As the Islamic economy is solely distinguished from other conventional economic systems in terms of the nature and the principles as well as the objectives it seeks to achieve, so, naturally, the aspects of monetary policy in the Islamic economy differ from the ones in the conventional economy in terms of concept, objectives and   instruments. Despite some points of agreement that can exist between them, the framework of an Islamic economy prohibits dealing in usury (RIBA) and substitutes its base on partnership (MUSHARAKA) as alternative to interest rate. Monetary policy tools are subdivided into  two groups : Group I: as neutral tools in the sense that it does not interfere with the base of partnership and it includes: quantitative tools, qualitative tools, and the tools and methods of immediate intervention Group II: as a list of tools based on usury with  the need of  development or enhancement  to be   useful in the framework of Islamic economy and the development of quantitative tools based on the interest rate, as well as qualitative  tools based on the interest rate.